CURRENT STATUS OF MOTHERS’ KNOWLEDGE ON CARING FOR CHILDREN UNDER 2 YEARS OLD WITH ACUTE DIARRHEA AT THAI BINH PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe mothers’ knowledge of caring for children under 2 years old with acute diarrhea at Thai Binh Pediatric Hospital.Methods: A cross-sectional descriptive study was conducted on 119 mothers of children under 2 years old with acute diarrhea, from September 2025 to April 2026. Data were collected using a 36-item questionnaire covering general information, knowledge of acute diarrhea, Oresol and fluid-electrolyte replacement, nutrition, hygiene, and medication use.Results: Mothers’ knowledge remained limited. The correct response rate for the definition of acute diarrhea was 45.4%; appropriate diet was 32.8%; and recognition of dehydration signs through skin turgor and sunken fontanel was 25.2% and 30.3%, respectively. Knowledge of Oresol was 45.4%, while correct understanding of preparation ranged from 37.8% to 78.2%. The proportions of correct knowledge regarding zinc supplementation and avoiding self-medication were 52.1% and 42.9%, respectively. Overall 68.9% of mothers had inadequate knowledge, while only 31.1% achieved the required level (≥ 75%).Conclusion: Mothers’ knowledge of caring for children with acute diarrhea remains insufficient, particularly in recognizing dehydration, nutritional management, and Oresol use. Health education interventions are needed to improve caregiving knowledge and practices.
Keywords: Acute diarrhea, knowledge, mothers, children under 2 years old, Thai Binh.